Hydrophobic modification of waterborne polymer slows urea release and improves nitrogen use efficiency in rice - Shen, Yazhen; Zhou, Jianmin; Du, Changwen; Zhou, Zijun (The Science of the total environment, 2021)
Controlled-release fertilizers (CRFs) with long release longevity have been actively sought to match the nutrient demands of crops over the entire growing period. Waterborne polymer is an environmental friendliness coating for CRFs because it neither uses organic solvent nor influences soil property. However, its low hydrophobicity leads to a short controlled-release longevity of CRFs coated with waterborne polymer. To overcome this drawback, a hydrophobic coating was fabricated using silica-modified fluorinated lauryl-methacrylate-containing polyacrylate (SFLPA). After hydrophobic modification, both a slower water influx rate and a larger modulus induced a reduced swelling rate and an extended controlled-release longevity consequently from 42 days to 108 days. Furthermore, a pot trial demonstrated that a single application of SFLPA-coated CRFs significantly boosted grain yield (by 13.36%), nitrogen uptake (by 17.44%) and nitrogen use efficiency (by 24.29%) compared to a three-split application of urea in rice production. The study demonstrated substantial potential of silica/fluorinated waterborne polymer for improving the effectiveness of CRFs in rice production. [Display omitted] •Waterborne polymer was dually modified by hydrophobic monomers and micro–nano silica.•After modification, the hydrophobicity of the coating was enhanced significantly.•The controlled-release longevity has been extended remarkably.•A clear improvement in rice yield and nitrogen use efficiency has been achieved.